Growth and structural characterisation of novel III-V semiconductor materials - Hall, Jacqueline Lesley (2010)
This thesis describes the growth and characterisation of four different III-V semiconductor materials. Growth was primarily performed by molecular beam epitaxy, while characterisation, which was largely structural, was carried out mainly using X-ray difraction and atomic force microscopy. Growth of low temperature(LT)GaAs was undertaken to investigate whether a phase transition accompanies the structural transition which occurs when GaAs is grown at temperatures below ~ 150C. It was found however, that LT GaAs remains zinc-blende, albeit with a signicant degree of disorder. Migration enhanced epitaxy was subsequently used to grow LT GaAs, resulting in single crystalline GaAs at growth temperatures down to 115C. The possibility of using AlN as a source for nitrogen, in the growth of GaAs based dilute nitrides was explored. No conclusive evidence has been presented to suggest that small amounts of nitrogen were incorporated into the GaAs lattice. The potential for ScN to be used as a buffer layer/interlayer to reduce the defect density in cubic GaN (c-GaN) was investigated. It was found that ScN grows on c-GaN(0 0 1)/GaAs(0 0 1) in a (1 1 1) orientation, leading to overgrowth of GaN occurring in the hexagonal phase. If the ScN interlayer was sufficiently thin (<3nm), then overgrowth of GaN was cubic, but no evidence of a reduction in stacking fault density was observed. Growth of ScN on GaAs(0 0 1) was also found to result mainly in a (1 1 1) orientation, but films were of poor quality. Growth of ScN on ScAs(0 0 1) was subsequently explored. ScN was found to grow in a (0 0 1) orientation, with both smoother surfaces and improved material quality than ScN(1 1 1). Growth of GaN atop ScN(0 0 1) was found to be c-GaN(0 0 1), but insuffcient studies have been carried out to determine the effect on material quality. During the growth of InGaN, it was found that unmounted substrates lead to large temperatures rises (>100C) for In rich compositions. Modelling heat absorption due to bandgap, phonon and plasmon absorption showed that this is due primarily to the large number of free carriers and not to the narrow bandgap (wrt substrate). The preliminary doping of In0.8Ga0.2N with Mn was investigated. The amount of Mn that can be incorporated without causing a signicant reduction in film quality was found to increase with decreasing growth temperature.